Knee prosthesis powered by a fully integrated and highly back-drivable electro-hydrostatic actuator. (May 2023) - Tessari, Federico; Galluzzi, Renato; Tonoli, Andrea; Amati, Nicola; De Michieli, Lorenzo; Laffranchi, Matteo
Abstract: In this paper, we propose the design and experimental validation of an electro-hydrostatic actuator, as an alternative to traditional actuation technologies, for a powered knee prosthesis. The aim is to demonstrate that the adopted system-level design yields a highly integrated, lightweight, back-drivable device able to satisfy the biomechanical torque and speed requirements of the knee. Moreover, the back-drivable nature of the actuators allows for active and regenerative operations in the four quadrants of the torque–speed plane. In the context of knee biomechanics, this could lead to a potential advantage with respect to other powered prosthetic solutions, in terms of power consumption and device autonomy. Different control strategies, such as position, admittance and regenerative braking controllers, are implemented and tested on a dedicated rig to validate the design choices and demonstrate the prosthesis functionality and performance. Highlights: A fully-integrated active knee prosthesis is presented. The electro-hydrostatic actuation principle is used. A prototype demonstrates the prosthesis functionality. The prototype shows advantages when compared to other solutions.